Synthesis of the biocompatible and highly stable MIL-127(Fe): from large scale synthesis to particle size control. Issue 22 (16th December 2015) - Chevreau, Hubert; Permyakova, Anastasia; Nouar, Farid; Fabry, Paul; Livage, Carine; Ragon, Florence; Garcia-Marquez, Alfonso; Devic, Thomas; Steunou, Nathalie; Serre, Christian; Horcajada, Patricia
Abstract : Controlled-sized crystals, from the nano to the microscale, of porous iron(iii ) 3, 3′, 5, 5′-azobenzenetetracarboxylate MOF have been successfully prepared with very high space-time-yields using different synthetic routes. Abstract : Controlled-sized crystals, from the nano to the microscale, of the biocompatible and highly stable porous iron(iii ) 3, 3, ′5, 5′-azobenzenetetracarboxylate MIL-127(Fe) MOF have been successfully prepared with very high space-time-yields using different synthetic routes.